2020
DOI: 10.3389/fchem.2020.00173
|View full text |Cite
|
Sign up to set email alerts
|

Non-cytotoxic Dityrosine Photocrosslinked Polymeric Materials With Targeted Elastic Moduli

Abstract: Controlling mechanical properties of polymeric biomaterials, including the elastic modulus, is critical to direct cell behavior, such as proliferation and differentiation. Dityrosine photocrosslinking is an attractive and simple method to prepare materials that exhibit a wide range of elastic moduli by rapidly crosslinking tyrosyl-containing polymers. However, high concentrations of commonly used oxidative crosslinking reagents, such as ruthenium-based photoinitiators and persulfates, present cytotoxicity conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 50 publications
(74 reference statements)
1
18
0
Order By: Relevance
“…To confirm whether any SAv-SAv crosslinking affects the interfaces of SAv tetramers, we prepared the hydrogel with the reduced reagent concentration to 31µM ruthenium and 15mM ammonium persulfate which minimized unspecific crosslinking between SAv tetramers (Figure S4). While the reduced concentration impacted the G′ as expected based on our previous report on ELP gels, 55 crossover frequency was not still observed (Figure 5d). Therefore, we concluded that, due to the high mechanical stability, the specifically self-associated, tetra-SAv in protein-network hydrogel behaves like a chemical cross-linker despite the fact that tetra-SAv is formed from non-covalent interactions.…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…To confirm whether any SAv-SAv crosslinking affects the interfaces of SAv tetramers, we prepared the hydrogel with the reduced reagent concentration to 31µM ruthenium and 15mM ammonium persulfate which minimized unspecific crosslinking between SAv tetramers (Figure S4). While the reduced concentration impacted the G′ as expected based on our previous report on ELP gels, 55 crossover frequency was not still observed (Figure 5d). Therefore, we concluded that, due to the high mechanical stability, the specifically self-associated, tetra-SAv in protein-network hydrogel behaves like a chemical cross-linker despite the fact that tetra-SAv is formed from non-covalent interactions.…”
Section: Resultssupporting
confidence: 84%
“…54 In our previous study, we used ELP with controlled numbers of tyrosine residues to modulate mechanical properties in photo-crosslinked protein-network materials. 55 We adapted the ELP sequence and further engineered to prepare A 2 YA 2 -A 48 -SAv artificial proteins ( Figure 5a ), where A and Y represent the five amino acid sequence, VPGXG with either alanine (A) and tyrosine (Y) in the X position, respectively. Therefore, offering only one site of photo-crosslinking at the end of each ELP arm, which is at the opposite terminus to the SAv physical cross-linkers (Figure 5a; Table S1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The employment of this photo-cross-linking reaction to improve the material properties of other tyrosine-containing hydrogels was also reported. 1070 1073 …”
Section: Materials and Devices Applications Of Pcetmentioning
confidence: 99%
“…Riboflavin (RB), also known as vitamin B2, is a non-toxic photoinitiator recently used for the preparation of silk fibroin hydrogels upon exposure to visible light. 7 A main limitation for the use of RB, however, is the slow gelation kinetics, 7,23,24 which would make this RB-based crosslinking not suitable for the encapsulation of cells within the hydrogel matrix. Here, we propose a method to achieve a fast and cytocompatible gelation of silk fibroin via RB-mediated crosslinking.…”
Section: Introductionmentioning
confidence: 99%